Towards the Design of a Smart Glasses Application for MICU Decision-Support: Assessing the Human Factors Impact of Data Portability & Accessibility. Issue 1 (September 2019) - Faiola, Anthony; Belkacem, Ilyasse; Bergey, Dani; Pecci, Isabelle; Martin, Benoit
The focus of this research is to develop and test a new smart glasses application for use in the medical intensive care unit (MICU) to support workflow, patient care, and overall clinical decision-making. The application prototype, mCARE glass, provides clinicians mobility, portability, and hands-free access to real-time patient electronic medical records and bedside data on demand. Five MICU physician volunteers participated in a study consisting of two parts: 1) a usability test with two tasks, and 2) an interview. Part one included usability testing with the use of the tracking pad, followed by the NASA Task Load Index Test and System Usability Scale test. Our findings suggest that mCARE glass has the potential to enhance clinical workflow in the ICU, and that besides providing easy access to patient data, it would improve patient monitoring and surveillance. Participants concurred that for mCARE glass to optimize clinical workflow, it must be well-integrated into one's daily work as part of decision-making and observation.